2009
DOI: 10.1051/0004-6361/200911708
|View full text |Cite
|
Sign up to set email alerts
|

Lucky Imaging of M subdwarfs

Abstract: Context. The knowledge of the binary properties of metal-poor and solar-metallicity stars can shed light on the potential differences between the formation processes responsible for both types of objects. Aims. The aim of the project is to determine the binary properties (separation, mass ratio, frequency of companions) for M subdwarfs, the low-metallicity counterparts of field M dwarfs, and investigate any potential differences between both populations. Methods. We have obtained high-resolution imaging in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…On the other hand, the frequency of VBs (a ≥ 10 AU) is markedly lower than for solar-metallicity stars (Allen, Poveda & Herrera 2000;Lodieu et al 2009;Zapatero Osorio & Martín 2004), though perhaps not for K-M dwarfs (Jao et al 2009). As a result, the total multiplicity frequency of Population II stars is CF The distribution of orbital period among solar-mass Population II multiple systems is characterized by a narrow peak in orbital period around log P ≈ 2-3, accompanied by a longperiod tail out to ∼ 10 4 AU that follows roughlyÖpik's law (Allen, Poveda & Herrera 2000) and a marked dearth of systems with orbital periods shorter than log P ≈ 1 , Rastegaev 2010.…”
Section: Population II Starsmentioning
confidence: 99%
“…On the other hand, the frequency of VBs (a ≥ 10 AU) is markedly lower than for solar-metallicity stars (Allen, Poveda & Herrera 2000;Lodieu et al 2009;Zapatero Osorio & Martín 2004), though perhaps not for K-M dwarfs (Jao et al 2009). As a result, the total multiplicity frequency of Population II stars is CF The distribution of orbital period among solar-mass Population II multiple systems is characterized by a narrow peak in orbital period around log P ≈ 2-3, accompanied by a longperiod tail out to ∼ 10 4 AU that follows roughlyÖpik's law (Allen, Poveda & Herrera 2000) and a marked dearth of systems with orbital periods shorter than log P ≈ 1 , Rastegaev 2010.…”
Section: Population II Starsmentioning
confidence: 99%
“…In addition, J12025+084 (M1.5 V; ζ = 0.898 -LHS 320) was classified by Gizis (1997) as an sdM2.0 star and was investigated extensively afterwards with high-resolution imagers (Gizis & Reid 2000;Riaz et al 2008;Jao et al 2009;Lodieu et al 2009). However, we failed to detect any subdwarf signpost in our high signal-to-noise spectrum, which is partly consistent with the metallicity [Fe/H] = −0.6±0.3 measured by Rajpurohit et al (2014).…”
Section: Metallicitymentioning
confidence: 99%
“…Deacon et al (2012a) also identified a T5.5 companion to the M4.5 dwarf LHS 2803, which was independently discovered by Mužić et al (2012). Subdwarfs are a rare subset of low-mass objects that have also received more attention with modern surveys (e.g., Riaz et al 2008;Lodieu et al 2009;Jao et al 2009). SDSS has spectroscopically identified a large sample of M type subdwarfs (e.g., Lépine 2009).…”
Section: The Field Populationmentioning
confidence: 99%
“…Subdwarfs are a rare subset of low-mass objects that have also received more attention with modern surveys (e.g., Riaz et al 2008;Lodieu et al 2009;Jao et al 2009). SDSS has spectroscopically identified a large sample of M type subdwarfs (e.g., Lépine 2009).…”
Section: The Field Populationmentioning
confidence: 99%